(untitled) (Journal of Dhaka Medical College, 2011)
Context: Eclampsia is one of the most leading causes of maternal deaths in developing countries. Many studies have demonstrated the relationship between hyperhomocysteinemia and eclampsia. The aim of this study was to examine the association between serum homocysteine with eclampsia. Methods: A case control study carried out in the Department of Biochemistry, Dhaka Medical College, Dhaka. 50 diagnosed cases of eclampsia were taken as cases and 52 healthy women with uncomplicated pregnancy were taken as controls. Serum homocysteine was measured in all study subjects by fluorescence polarization immunoassay (FPIA) method. Result: Serum homocysteine found to be significantly increased (p<0.001) in patients with eclampsia (10.44±4.08 μmol/L) compared to controls (7.97±3.46 μmol/L). Conclusion: It can be concluded that elevated serum homocysteine is associated with eclampsia. Key words: Serum homocysteine; eclampsia. DOI: 10.3329/jdmc.v19i2.7085 J Dhaka Med Coll. 2010; 19(2) : 131-134